Silicon dioxide as an efficient adsorbent in the degumming of rapeseed oil. (20th September 2020) - Yao, Yingzheng; Liu, Changsheng; Xiong, Wei; Liang, Qiang; Xuan, Pu; Zeng, Xiaodan; Zeng, Shiqin; Zhou, Qi; Huang, Fenghong
Abstract: Traditional degumming techniques used in the edible oil industry require high temperatures and consume more energy. As a result, green refining techniques are required to be developed. Rapeseed oil is one of the preferred edible oils used in southwest China because of its unique flavor. However, the dark color of the oil is an element of concern. It is important to find a refining method that can improve the color of the oil while retaining its flavor. The main purpose of this study was to evaluate a low-energy consumption degumming method that used different dosages (0.5%, 1.5%, 2.5%, and 3.5% w/w) of silicon dioxide when applied to rapeseed oil. The concentration of phospholipids, total phenolic content including that of canolol, and the color, flavor profile, acid value, chlorophyll content, and oxidative stability of the rapeseed oil were analyzed to evaluate the degumming effect of silicon dioxide. It was observed that the adsorption by silicon dioxide eliminated up to 85% of phospholipids from crude rapeseed oil, retained up to 96% of the total phenolic content, and had little effect on the amount of canolol, which is the dominant phenolic compound in rapeseed oil. In addition, the method improved the color of rapeseed oil by increasing the L∗/neutral value and decreasing the a∗/red values, and had little effect on the flavor according to E-nose. Using silicon dioxide as the adsorbent reduced the acid value and chlorophyll content of the oil, apart from largely shortening its induction period. When the recommended silicon dioxide dosage of 1.5% (w/w) was used, phospholipids, total phenolic content, a∗, and red values decreased by 81%, 5%, 38.2%, and 12.7%, while the L∗ and neutral values increased by 9.8% and 28.6%. This technology is economical and environmentally friendly due to its mild reaction conditions and zero wastewater production. It provided a new strategy and showed a great potential in the degumming of rapeseed oil. Highlights: Silicon dioxide shows great potential for crude rapeseed oil degumming by adsorbing. It could remove 85% of phospholipids and retain 96% of total phenolic content. It is an economical and environmental friendly refining method with mild conditions.